DEVELOPMENT OF MEGA BUANA HOSPITAL MANAGEMENT INFORMATION SYSTEM (SIMRS) - Malik, Abdul; Jamilah, Nur; Kurniawan, Fahmi; Ma’arif, Syamsul; Aswin (Bahasa Indonesia, 2025)
The Hospital Management Information System (SIMRS) is a technology-driven solution designed to enhance healthcare service efficiency by optimizing patient data management and expediting hospital administrative processes. This article discusses the development of SIMRS at Mega Buana Hospital by employing a user-based needs approach and integrating the latest technology to ensure optimal functionality for medical personnel and administrative staff. This research utilizes a needs analysis method, system development following the SDLC (System Development Life Cycle) model, including design, implementation, and system performance evaluation. The results indicate that SIMRS significantly improves hospital operational efficiency, minimizes administrative errors in patient data and medical record management, and accelerates patient services across various hospital units.